SPECIFIC FEATURES OF ENSURING FINANCIAL SECURITY OF INSURANCE COMPANIES (World Bulletin of Management and Law, 2025)
The article examines the economic content and importance of ensuring the financial security of insurance companies. The economic environment of the insurance industry, its sensitivity to changes, as well as the scientific and practical aspects of ensuring the stability of insurance companies through financial and statistical analysis are comparatively studied. Also, the financial security of insurance companies has a significant impact not only on the industry itself, but also on the national economy, therefore, this article develops proposals and recommendations aimed at strengthening the insurance system in the economies of countries.